(untitled) (Geologica Macedonica, 2013)
The data presented in the paper were obtained based on analyses carried out on samples collected from various depths along the entire length of drill-hole no. 4. The drill-hole was the last one made in the area of the Plavica deposit by the Rio Tinto Company. The samples analyzed point out the presence of subvolcanic to volcanic rocks, presumably dacites and daciteandesites, that can be distinguished based on the presence of primary quartz. An exception is sample no. 6 which, most probably, represents one of the vein rocks. The alterations seen under a microscope include silicification (with several quartz generations), argillitisation, sericitisation, epidotisation, K-metasomatism and, presumably, zeolitization. X-ray examinations determined the alterations as follows: silicification, alunitisation, argillitisation, sericitisation, K-feldspatisation, fluoritisation, propylitisation and hematisation.